Digital speech coding for low bit rate communication systems - Kondoz, A.M (John Wiley & Sons, 1994)
Speech communication is still the dominant service in telecommunications networks. However, modern information requirements, such as multimedia, satellite and mobile communications, have created the need for a more robust and flexible alternative to the traditional analogue system. Digital speech transmission offers many advantages over its analogue counterpart, including consistent quality, versatility, security and successful integration into ISDN. This topical book provides an in-depth account of the latest developments in digital speech coders specifically designed for use in the evolving communications systems.